Social Issues in Nepal (2018–2026) Affecting Human Resource Practices at The Organizational and Societal Level - Karki, Sarala; Ojha, Sateesh Kumar (SADGAMAYA, 2026)
This article talks about the source "society," which is where the human resources in society and organizations come from. This study analyzes collective behavior in Nepal from 2018 to 2025 using several sociological frameworks and emphasizes Digital Media Observation (DMO) as a proactive approach to human resource management. In this sense, societies exercise real human resource management and development inside their own culture. It concludes that political instability and inadequate governance upset the balance of society because of unfairness in the workplace and in institutions. Youth-led protests show how unemployment and income disparity affect people. Structural lag, which happens when institutions don't change quickly enough, makes tensions worse, and poor remedies, like limiting social media, make discontent worse. Bad management and insufficient enforcement of labor laws make turnover higher.